Trismus surgical release and free flap reconstruction after radiation therapy in oral and oropharyngeal squamous cell carcinoma. Issue 2 (22nd August 2017) - de Pablo, Alba; Chen, Yu‐Ting; Chen, Jyh‐Kwei; Tsao, Chung‐Kan
Abstract : Background and Objectives: This study aims to review our experience in trismus release followed by free flap reconstruction after radiotherapy in oral and oropharyngeal cancer, describe the results obtained in long‐term follow‐up and identify possible predictors of outcome. Methods: Patients' demographics, tumor characteristics and treatment where retrieved. Surgical release and reconstructive procedures were detailed. Interincisor distances (IIDs) where measured preoperatively (PO‐IID), intraoperatively after release (IO‐IID) and in the last follow‐up (FU‐IID). Potential predictors of outcome in terms of interincisor long‐term gain (LT‐gain) and postoperative loss (PO‐loss) were analyzed. Results: Twenty‐eight patients were included in our study. The mean LT‐gain was 8.9 ± 7.0 mm, and the PO‐loss was 22.14 ± 7.27 mm. Patients with a PO‐IID of 10 mm or less had a significant higher LT‐gain ( P = 0.038). Predictors of worse outcome included having received a previous maxillectomy during tumor ablation (lower LT‐gain, P = 0.035), and previous buccal mucosa resection (higher PO‐loss, P = 0.044). Conclusions: Trismus release and free flap reconstruction after radiotherapy in oral and oropharyngeal cancer patients seems to be associated with modest long term results and a high incidence of trismus recurrence, particularly in cases of prior buccal resections or maxillectomy. Patients should be adequately informed and carefully selected before indicating the procedure.